ECOLOGIA DA ICTIOFAUNA DE TRÊS CANAIS DE MARÉ DA BAÍA DE SÃO MARCOS, MA, BRASIL - LIMA, Leny Claudia Penha de (2013)
This paper presents a spatial analysis of fish diversity of the Bay of São Marcos, in northern Maranhão, besides using a guild approach to the description of the ichthyofauna assemblies. This approach enables a clearer understanding of the role of species in their habitats, and allows comparison with other environments. The ichthyofauna was sampled in three tidal channels, with two of them located on the island of Sao Luis and another on Crab Island. Fish were collected using weir and waiting nets, kept on ice and immediately transported to the laboratory. 59 species were identified, distributed to 10 orders and 26 families, representing a total of 19,910 individuals. The Ariidae family stood out as most specious Sciades herzbergii being the most abundant at all sampling points. The Index of Relative Importance (IRI) defined as dominant species Sciades herzbergii, Anableps anableps, Colomesus psittacus and Cathorops spixii. The richness estimators indicated that communities are quite heterogeneous, with high participation of rare species in relation to the number of abundant species. The highest values for diversity estimators were observed in tidal channel Tronco, located on the island of Carangueijos, there are significant differences in the relative contribution of species in community composition between this and other estuaries studied on the island of São Luís. Sciades herzbergii, Anableps anableps, Cathorops spixii, Notarius bonillai and Mugil curema were the species that contributed most to the dissimilarity between areas. Considering all sampling areas, estuarine species had higher contribution to the composition of fish assemblages, representing 46% of the total pattern frequently observed in tropical estuaries. With respect to trophic groups, zoobentívoros accounted for 53% of all individuals in the study area; omnivores and herbivores were less abundant in all categories tidal channels studied. The results indicate changes in the structure of assemblies of estuarine fish when compared with previous studies in the region.